Implementation of Restorative Justice in the Rembang District Attorney's Office Based on Prosecutor's Regulation Number 15 of 2020 Concerning Termination of Prosecution Based on Restorative Justice - Pramesti, Treninda Ardea; Winjaya Laksana, Andri (UNISSULA Semarang, 2025)
Abstract. Regulation of the Attorney General of the Republic of Indonesia Number 15 of 2020 concerning Termination of Prosecution Based on Restorative Justice is implemented on the basis of case resolution that emphasizes restoration to the original state and not with retaliation. This regulation emphasizes using conscience in resolving cases. The purpose of this study is to determine how the implementation of the termination of prosecution of fraud crimes is based on restorative justice, what are the obstacles, and how effective the implementation of restorative justice is in resolving fraud crimes at the Rembang District Attorney's Office. The research aproach used in this study is an empirical legal aproach method with a descriptive research type. The problem aproach used is to use primary and secondary data obtained from literature studies and field studies at the Rembang District Attorney's Office, then data processing is carried out by evaluating data, classifying data, and systematizing data, then analyzing it using qualitative analysis. The results of the study indicate that the implementation of the termination of prosecution in criminal acts of fraud based on restorative justice at the Rembang District Attorney's Office runs in accordance with aplicable laws and regulations and reaches an agreement between the victim and the perpetrator. As for the most dominant obstacle if the victim and the suspect do not reach an agreement to forgive each other and the suspect provides compensation or restitution. Regarding the effectiveness of the implementation of restorative justice at the Rembang District Attorney's Office, it runs well, marked by the achievement of restorative justice between the victim and the suspect.